Kinematic reworking and exhumation within the convergent Alpine orogen - Reddy, Steven; Wheeler, J.; Bulter, R.; Cliff, R.; Freeman, S.; Inger, S.; Pickles, C.; Kelley, S. (Elsevier, 2003)
Kinematic data from the internal zones of the Western Alps indicate both top-to-SE and top-to-NW shearing during syn-kinematic greenschist facies recrystallisation. Rb/Sr data from white micas from different kinematic domains record a range of ages that do not represent closure through a single thermal event but reflect the variable timing of syn-kinematic mica recrystallisation at temperatures between 300-450?C. The data indicate an initial phase of accretion and foreland-directed thrusting at c. 60 Ma followed by almost complete reworking of thrust-related deformation by SE-directed shearing. This deformation is localised within oceanic units of the Combin Zone and the base of the overlying Austroalpine basement and forms a regional scale shear zone that can be traced for almost 50 km perpendicular to strike. The timing of deformation in this shear zone spans 9 Ma from 45-36 Ma. The SE-directed shear leads to local structures that cut upwards in the transport direction with respect to tectonic stratigraphy, and such structures have been interpreted in the past as backthrusts in response to ongoing Alpine convergence. However, on a regional scale the top-to-SE deformation is related to crustal extension, not shortening, and is coincident with exhumation of eclogites in its footwall. During this extension phase, deformation within the shear zone migrated both spatially and temporally giving rise to domains of older shear zone fabrics intercalated with zones of localised reworking. Top-NW kinematics preserved within the Combin Zone show a range of ages. The oldest (48 Ma) may reflect the final stages of emplacement of Austroalpine Units above Piemonte oceanic rocks prior to the onset of extension. However, much of the top-to-NW deformation took place over the period of extension and may reflect either continuing or episodic convergence or tectonic thinning of the shear zone.40Ar/39Ar data from the region are complicated due to the widespread occurrence of excess 40Ar in eclogite facies micas and partial Ar loss during Alpine heating. Reliable ages from both eclogite and greenschist facies micas indicate cooling ages in different tectonic units of between 32-40 Ma. These ages are slightly younger than Rb/Sr deformation ages and suggest that cooling below c.350?C occurred after juxtaposition of the units by SE-directed extensional deformation.Our data indicate a complex kinematic history involving both crustal shortening and extension within the internal zones of the Alpine orogen. To constrain the palaeogeographic and geodynamic evolution of the Alps requires that these data be integrated with data from the more external zones of the orogen. Complexity such as that described is unlikely to be restricted to the Western Alps and spatially and temporally variable kinematic data are probably the norm in convergent orogens. Recognising such features is fundamental to the correct tectonic interpretation of both modern and ancient orogens.